The potential roles for adipose tissue in peripheral nerve regeneration. Issue 1 (7th September 2015) - Walocko, Frances M.; Khouri, Roger K.; Urbanchek, Melanie G.; Levi, Benjamin; Cederna, Paul S.
Abstract : Introduction: This review summarizes current understanding about the role of adipose‐derived tissues in peripheral nerve regeneration and discusses potential advances that would translate this approach into the clinic. Methods: We searched PubMed for in vivo, experimental studies on the regenerative effects of adipose‐derived tissues on peripheral nerve injuries. We summarized the methods and results for the 42 experiments. Results: Adipose‐derived tissues enhanced peripheral nerve regeneration in 86% of the experiments. Ninety‐five percent evaluated purified, cultured, or differentiated adipose tissue. These approaches have regulatory and scaling burdens, restricting clinical usage. Only one experiment tested the ability of adipose tissue to enhance nerve regeneration in conjunction with nerve autografts, the clinical gold standard. Conclusion: Scientific studies illustrate that adipose‐derived tissues enhance regeneration of peripheral nerves. Before this approach achieves clinical acceptance, fat processing must become automated and regulatory approval achieved. Animal studies using whole fat grafts are greatly needed for clinical translation. © 2015 Wiley Periodicals, Inc. Microsurgery 36:81–88, 2016.